Case report: Emergency treatment of late-presenting congenital diaphragmatic hernia with tension gastrothorax in three Chinese children - Guo, Rui; Zhang, Lina; Zhang, Shisong; Xu, Hongxiu; Zhai, Yunpeng; Zhao, Huashan; Lv, Longfei (Frontiers in Pediatrics, 2023)
Background: Congenital diaphragmatic hernia (CDH) is a scarce birth defect. It is called late-presenting CDH when symptoms are found after one month of life. The clinical manifestations of late-presenting CDH are diverse, among which the most fatal is the cardiac arrest caused by tension gastrothorax. The disease is rare, can easily lead to death owing to improper emergency treatment. This report illustrates the emergency treatment of late-presenting CDH with tension gastrothorax in three Chinese children. Case reports and management: Three children presented to emergency room with a sudden dyspnea, diagnosed accurately by X-ray or computed tomography. In case 1, the gastric tube could not be inserted at the first attempt, and the child cried incessantly. Cardiac arrest occurred when the gastric tube was re-inserted. After cardiopulmonary resuscitation and placement of a thoracic drainage tube, a large amount of gas and stomach contents were drained. Laparoscopic surgery was performed. The patient died of sepsis. In case 2, the gastric tube could not be inserted at the first attempt; consequently, emergency surgery was considered instead of retrying. After the patient was anesthetized, a gastric tube was successfully placed. Subsequently, a large amount of gas and gastric contents was drained, and thoracoscopic surgery was performed. The patient recovered evenly. In case 3, the gastric tube was successfully inserted at the first attempt; however, the vital signs were unstable due to poor drainage of the gastric tube. We injected 20 mL of iohexol into the stomach tube for angiography and dynamic chest film monitoring. After adjusting the position of the stomach tube, the stomach collapsed completely. Thoracoscopic surgery was performed. The patient recovered evenly. Conclusion: Early diagnosis is essential for children with late-presenting CDH complicated by tension gastrothorax. Fully collapsing the stomach is a key step in emergency treatment. In addition, gastric tube insertion is the first choice. In children with difficulty in gastric tube placement at the first attempt, the gastric tube can be placed under anesthesia, and emergency surgery performed simultaneously. Endoscopic surgery can be the first choice in cases of complete stomach collapse.